FOMO-Based Consumption Behavior in Islamic Economics Review (Study of Mukbang Behavior Among Generation Z in Pontianak City - Nurjannah, Syamratun (Yayasan Rahmat Islamiyah, 2025)
FOMO (Fear of missing out) among generation Z is a trend that can be observed not only on social media networks but has also become a positive behavior in social settings such as mukban. This FOMO trend has become something referentative for self-image rather than just following along. Each individual has constructed himself as he understands the concept of FOMO.This article uses a qualitative perspective and data was obtained through observation and in-depth interviews. The informants were five people aged between 25 and 27 years old and belonged to the generation Z category. The argument of this article is that FOMO cannot be fully understood as a negative behavior, but also as a means of self-engagement to be part of a very digital life.Thus, this article has implications for the understanding of the concept of FOMO, which is constantly evolving along with the impact of digitalization on the social relations of generation Z. These social relations cannot be understood in terms of compulsive behavior in terms of consumption but also provide benefits in terms of self-identification with the social environment.